Audit of the tax revenue management process of the center of commune II in the district of Bamako : case of the fight against tax corruption - DIALLO , HOUDOU ATTIKOU; DIALLO , SIDI MAMADOU (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The objective of this research is to understand the notion of tax corruption and tax evasion, to make the internal control system more efficient, of the procedures for collecting tax revenue, and also to familiarize with the diversity of the fields of analysis required by the determinants of tax fraud and corruption. It is a research based on a positivist epistemological positioning and a mixed and abductive. Methodological approach with regard to the analysis of our various finance laws, our results show that there is a significant link between, tax and public finance, better managing your taxation means better managing your finances which means better securing the tax revenue against tax evasion and corruption in order to meet the expenses payable by the state. Through this article, we will conduct a mediation on the cause-and-effect relationships of corruption on fraud, and that of the shared responsability of the various actors in the fight against tax fraud, the audit function and the tax administration.